Analisis Pengaruh Lingkungan Kerja dan Budaya Kerja Terhadap Komitmen Organisasi - Saputra, Syafiq Aryanta Manggala; Karyadi, Sugeng; Usmia, Sitti; Pujiastuti, Endah; Setiawan, Roy (Jurnal EMT KITA, 2025)
The purpose of this research is to analyze and test the influence of work environment and organizational culture on organizational commitment. This research uses a quantitative method with regression analysis. The sampling technique uses a census and a sample size of 96 employees was obtained by distributing questionnaires to employees. The data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this research show that the organizational environment and organizational culture, both partially and simultaneously, have a positive and significant effect on organizational commitment. The results of this research can be used as evaluation material for companies to pay more attention to organizational commitment so that employee performance can be improved.